Differential response of SHH-expressing adult medulloblastomas to the sonic hedgehog inhibitor vismodegib: whole-genome analysis. Issue 11 (2nd November 2019) - Lou, Emil; Nelson, Andrew C.; Kool, Marcel
ABSTRACT: Medulloblastoma is an aggressive primitive neuroectodermal tumor of the cerebellum that is more common in children than in adults. In the past decade, advances in understanding the molecular drivers of medulloblastoma have identified four molecular subgroups defined by experimental gene expression profiles: the WNT pathway, sonic hedgehog (SHH) pathway, and subgroups 3 and 4 (non-SHH/WNT). Medulloblastoma of adults belong primarily to the SHH category. Vismodegib, an SHH-pathway inhibitor, FDA-approved in 2012 for treatment of basal cell carcinoma, has been used successfully in the setting of chemorefractory medulloblastoma, but not as a first-line therapy. In 2016, we reported a case of an adult patient with a sustained response of an unresectable multifocal form of adult medulloblastoma to vismodegib. Molecular analysis in that case revealed mutations in TP53 and a cytogenetic abnormality, i17q, that is prevalent and most often associated with subgroup 4 rather than the SHH-activated form of medulloblastoma. Here, we report further whole-genome analysis of that patient (designated Patient A) as well as an additional adult patient (Patient B) whose tumor harbored the SHH molecular subgroup but which was unresponsive to visgmodegib therapy. Comparison of these disparate responses highlights the challenges to tailoring SHH-targeted treatment in individual patients with adult medulloblastoma.